INDUCIBLE CLINDAMYCIN RESISTANCE IN METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - ARUNAVA KALI; S. STEPHEN; S. UMADEVI (International Journal of Pharma and Bio Sciences, 2013)
Inducible clindamycin resistance in Staphylococcus aureus is of great concern owing to its frequent association with false sensitivity in antibiogram and treatment failure. One hundred and two clinical isolates of Methicillin resistant S. aureus (MRSA) were identified by oxacillin, cefoxitin disc diffusion and oxacillin agar dilution method. Antibiotic susceptibility to erythromycin and clindamycin was detected by Kirby Bauer disc diffusion method. Isolates resistant to erythromycin were further tested by D test for detection of inducible clindamycin resistance. MRSA strains had high resistance to erythromycin (74.5%). Inducible clindamycin resistance was detected in 49.2% and 30.7% MRSA isolated from inpatients & outpatients and in 40% and 43.5% MRSA isolated during 2004-2009 and 2010-2011, respectively. Owing to high prevalence of inducible clindamycin resistance in MRSA, we recommend routine testing for inducible clindamycin resistance in laboratories.